The Difference between Earnings and Operating Cash Flow as an Indicator of Financial Reporting Fraud* - LEE, THOMAS A.; INGRAM, ROBERT W.; HOWARD, THOMAS P. (Contemporary Accounting Research, 1999)
Abstract This paper examines the relation between earnings and operating cash flow to derive and test an indicator of financial statement fraud. Accrual measurement concepts indicate that financial statement fraud should be associated with high levels of earnings relative to operating cash flow. We demonstrate that the excess of earnings over operating cash flow is extreme in most fraud cases in years immediately prior to the fraud discovery based on a sample of 56 fraud cases from 1978 to 1991. We compare the distribution of the earnings minus operating cash flow variable for fraud firms with that for a sample of 60,453 firm‐years for firms listed on COMPUSTAT. We test a logistic regression model in which the discovery/nondiscovery of fraud is the dependent variable, and earnings minus operating cash flow is the explanatory variable. Other control variables are included in the model based on prior studies. Results are consistent with expectations derived from accrual measurement theory. We then examine the predictive ability of the model using our sample of fraud firms and a sample of nonfraud firms in the same four‐digit SIC code industries. Observations for the fraud firms are for the fiscal year prior to the discovery of fraud. Observations for the nonfraud firms are for the same fiscal years as the fraud firms in the same industries. The predictive ability of the model, including the excess of earnings over operating cash flow, is substantially higher than the predictive ability of the model omitting this variable. We conclude that the earnings‐operating cash flow relation provides important information for those interested in identifying financial statement fraud, especially when considered in conjunction with other factors associated with fraud risk.